SPIRIT OF EXISTENTIALISM IN HEMINGWAY’S FOR WHOM THE BELL TOLLS - RASYID RIDHO HAMIDY (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
Several studies on English Literature have been conducted by few students of theEnglish Education Program. In this study the writer tries to analyze Hemingway’s ForWhom the Bell Tolls (1940) with philosophical approach. In this approach the novel isbelieved to have philosophical values. Further, for the novel seems to havephilosophical values similar to ones of existentialism, the writer tries to find outwhether it really has spirit of existentialism. The method which is applied in thisresearch is a descriptive qualitative approach. The data being analyzed aredescriptive data in form of written words which need interpretation because this studydeals with philosophical approach in For Whom the Bell Tolls. The result of this studyshows that a true man must accomplish his task and he should not hope anything forhimself. Even though in a defeat, he still can make the most of his life by committingsome worthwhile acts for him and others too. And the novel has the spirit ofexistentialism as shows by the main character and the themes. Completing the study,the writer suggests the readers and the students English Education Program of IKIPMataram; study the biography of the author and socio-cultural background of the novelbefore studying it; study the novel with the emphasis on other aspect; and loveliterature.Key Words: Intrinsic Aspects, Existentialism, Spirit.Beberapa penelitian di Sastra Inggris telah dilakukan oleh beberapa mahasiswaProgram Pendidikan Bahasa Inggris. Dalam penelitian ini penulis mencoba untukmenganalisis novel Hemingway yang berjudul For Whom the Bell Tolls (1940) denganpendekatan filosofis. Dalam pendekatan ini, diyakini novel ini memiliki nilai-nilaifilosofis. Selanjutnya, novel ini tampaknya memiliki nilai filosofis mirip dengan yangeksistensialisme, penulis mencoba untuk mencari tahu apakah benar-benar memilikisemangat eksistensialisme. Metode yang digunakan dalam penelitian ini adalahpendekatan deskriptif kualitatif. Data yang dianalisis adalah data deskriptif berupakata-kata tertulis yang perlu penafsiran karena penelitian ini berkaitan denganpendekatan filosofis dalam For Whom the Bell Tolls. Hasil penelitian ini menunjukkanbahwa seorang pria sejati harus menyelesaikan tugas dan ia seharusnya tidakberharap apa-apa untuk dirinya sendiri. Meskipun kalah, dia masih bisa membuatsebagian besar hidupnya dengan melakukan beberapa tindakan yang bermanfaatbagi dirinya dan orang lain juga. Dan novel memiliki semangat eksistensialismesebagai menunjukkan oleh karakter utama dan tema. Menyelesaikan pendidikannya,penulis menyarankan pembaca dan siswa Program Pendidikan Bahasa Inggris IKIPMataram; mempelajari biografi penulis dan latar belakang sosial-budaya novelsebelum mempelajarinya; mempelajari novel dengan penekanan pada aspek-aspeklain; dan cintailah sastra.Kata Kunci: Aspek Intrinsik, Eksistensialisme, Semangat.